Hubungan Pola Asuh Otoritatif dan Kontrol Diri dengan Sikap Remaja Terhadap Perilaku Seks Bebas - Dwi Adhinda Junaidi Putri (Consilium : Berkala Kajian Konseling dan Ilmu Keagamaan, 2019)
Attitude is an evaluative response. Authoritative parenting and self-control is a factor that are factors that may have influenced the adolescent`s attitude towards free sex. This study aimed to describe: (1) the correlation of  authoritative parenting with adolescent`s attitude towards free sex, (2) the correlation of of self-control with adolescent`s attitude towards free sex, and (3) the correlation of authoritative parenting and self-control with adolescent`s attitude towards free sex. This study used quantitative research which applied correlational approach. The population of the research was the student’s in SMA N 1 Stabat. By using proportional random sampling technique, 172 student’s were chosen as the sample. The instrument of the research was the scale of  Likert. The instrument of the research was a scale. The purpose of the research was analyzed by using simple linear regression technique, and multiple linear regression technique. The results of the research revealed that: (1) there was a correlation between authoritative parenting with adolescent`s attitude towards free sex, (2) there was a correlation between self-control with adolescent`s attitude towards free sex, and (3) there was a correlation between authoritative parenting and self-control simultaneously with adolescent`s attitude towards free sex.